ONE-HELIX PROTEIN2 (OHP2) Is Required for the Stability of OHP1 and Assembly Factor HCF244 and Is Functionally Linked to PSII Biogenesis. Issue 4 (21st June 2018) - Hey, Daniel; Grimm, Bernhard
Abstract : The two Arabidopsis thaliana one-helix proteins form a trimeric complex with the PSII assembly factor HCF244 and contribute to the synthesis and assembly of the PSII core subunits. Abstract: The members of the light-harvesting complex protein family, which include the one-helix proteins (OHPs), are characterized by one to four membrane-spanning helices. These proteins function in light absorption and energy dissipation, sensing light intensity, and triggering photomorphogenesis or the binding of chlorophyll and intermediates of chlorophyll biosynthesis. Arabidopsis ( Arabidopsis thaliana ) contains two OHPs, while four homologs (named high-light-induced proteins) exist in Synechocystis PCC6803. Various functions have been assigned to high-light-induced proteins, ranging from photoprotection and the assembly of photosystem I (PSI) and PSII to regulation of the early steps of chlorophyll biosynthesis, but little is known about the function of the two plant OHPs. Here, we show that the two Arabidopsis OHPs form heterodimers and that the stromal part of OHP2 interacts with the plastid-localized PSII assembly factor HIGH CHLOROPHYLL FLUORESCENCE244 (HCF244). Moreover, concurrent accumulation of the two OHPs and HCF244 is critical for the stability of all three proteins. In particular, the absence of OHP2 leads to the complete loss of OHP1 and HCF244. We used a virus-induced gene silencing approach to minimize the expression of OHP1 or OHP2 in adult Arabidopsis plants and revealed that OHP2 is essential for the accumulation of the PSII core subunits, while the other photosynthetic complexes and the major light-harvesting complex proteins remained unaffected. We examined the potential functions of the OHP1-OHP2-HCF244 complex in the assembly and/or repair of PSII and propose a role for this heterotrimeric complex in thylakoid membrane biogenesis.